Sex differences in athlete"s heart are evident from early adolescence. (4th February 2022) - Forsaa, M; Bjerring, AW; Haugaa, KH; Hallen, J; Sarvari, S; Edvardsen, T
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): South-Eastern Norway Regional Health Authority OnBehalf: ProCardio Center for Innovation Introduction: Athlete's Heart (AH) is characterized by cardiac remodelling as a response to exercise, but data on sex differences in adolescent athletes is limited. Purpose: To study the impact of sex on development of AH in adolescent athletes. We hypothesize that male adolescent athletes develop greater morphological changes than females, also when adjusted for body surface area (BSA). Methods: We recruited 12-year-old cross-country skiers of both sexes in a longitudinal cohort study. We examined them with echocardiography at age 12, 15 and 18. Results: We recruited 76 athletes (48 males and 28 females). We could follow 48 participants at age 15 (34 males and 14 females), and 34 participants at age 18 (23 males and 11 females). There were no sex differences in exercise hours at any time point. Adolescent males had greater indexed LV end-diastolic volume (LV EDVi) at all time points (Figure 1). Both sexes displayed LV enlargement already at age 12, and athletes of both sexes displayed LV EDVi close to or above upper reference values for the adult population. Only males increased their indexed LV mass (LVMI) from 12 to 18 years (LVM/BSA,  Δg/m²; 33 ± 27 vs 4 ± 19, P = 0.006). Male adolescent athletes increased their LVMI by 7.4 grams more and LV EDVi by 4.0 ml more than female athletes did for every 1000 hours of exercise training. Cardiac function was within normal range in both sexes throughout the study period. Conclusion:  Sex-related differences in cardiac adaptation to exercise are evident from early adolescence. Both sexes demonstrate cardiac remodelling, but adolescent male athletes display greater morphological changes compared to female athletes.